Cryptocurrencies:Amodernmythorthecurrencyoffuture (International Journal of Food and Nutritional Sciences, 2022)
This article investigates the evolution of cryptos and if they could serve as a modern myth or futures money. In recent years, digital currencies such as bitcoin and Ethereum have drawn a lot of attention, with some speculators predicting they would eventually replace fiat currencies. Others counter that cryptocurrencies are merely speculative investments with no real intrinsic value. This article explores the mechanics and history of digital currencies and assesses their potential as a brand-new form of money. It examines cryptocurrency’s decentralisation, security, and volatility, as well as its advantages and disadvantages when used for trade and investment. The effects of virtual currencies on the world financial system are also examined, including the risk of disruption and any regulatory issues. Ultimately, the goal of this paper is to present a fair viewpoint on the prospects for cryptos and how they might change the way we view money. It is obvious that virtual currencies have so far had a considerable impact on the world of finance and may do so in the years to come, despite the fact that there are still a lot of uncertainties and hazards attached to them.